Comparative Chloroplast Genome Analyses of the Winter-Blooming Eastern Asian Endemic Genus Chimonanthus (Calycanthaceae) With Implications For Its Phylogeny and Diversification - Jamal, Abbas; Wen, Jun; Ma, Zhi-Yao; Ahmed, Ibrar; Abdullah,; Chen, Long-Qing; Nie, Ze-Long; Liu, Xiu-Qun (Frontiers in Genetics, 2021)
Chimonanthus of Calycanthaceae is a small endemic genus to China, with unusual winter-blooming sweet flowers widely cultivated for ornamentals and medicinal uses. The evolution of Chimonanthus plastomes and its phylogenetic relationships remain unresolved due to limited availability of genetic resources. Here, we report fully assembled and annotated chloroplast genomes of five Chimonanthus species. The chloroplast genomes of the genus (size range 153,010 – 153,299 bp) reveal high similarities in gene content, gene order, GC content, codon usage, amino acid frequency, simple sequence repeats, oligonucleotide repeats, synonymous and non-synonymous substitutions, and transition and transversion substitutions. Signatures of positive selection are detected in atpF and rpoB genes in C. campanulatus. The correlations among substitutions, InDels, and oligonucleotide repeats reveal weak to strong correlations in distantly related species at the intergeneric levels, and very weak to weak correlations among closely related Chimonanthus species. Chloroplast genomes are used to reconstruct a well resolved phylogenetic tree, which supports the monophyly of Chimonanthus. Within Chimonanthus, C. praecox and C. campanulatus form one clade, while C. grammatus C. salicifolius, C. zhejiangensis, and C. nitens constitute another clade. Chimonanthus nitens appears paraphyletic and is closely related to C. salicifolius and C. zhejiangensis, suggesting the need to reevaluate the species delimitation of C. nitens. Chimonanthus and Calythanthus diverged in mid-Oligocene; the radiation of extant Chimonanthus species was dated to the mid-Miocene, while C. grammatus diverged from other Chimonanthus species in the late Miocene. C. salicifolius, C. nitens (a) and C. zhejiangensis are inferred to have diverged in the Pleistocene of the Quaternary period, suggesting recent speciation of a relict lineage in the subtropical forest regions in eastern China. This study provides important insights into the chloroplast genome features and evolutionary history of Chimonanthus and family Calycanthaceae.